Cloud-base and cloud-top heights determined from a ground-based cloud radar in Beijing, China. (15th March 2019) - Zhou, Qing; Zhang, Yong; Li, Bai; Li, Liangxu; Feng, Jinming; Jia, Shuze; Lv, Shanshan; Tao, Fa; Guo, Jianping
Abstract: The cloud structure determined from ground-based measurements is generally important to the better understanding of the climate system. This study examines vertically-resolved cloud structures and their characteristics over Beijing using one year (1 December 2016 to 30 November 2017) of ground-based Ka-band (35 GHz) millimeter-wave cloud radar (MMCR) measurements. MMCR-derived cloud-base heights (CBHs) and cloud-top heights (CTHs) are compared with those derived from a Vaisala CL51 ceilometer (CL51) and those retrieved from the Himawari-8 geostationary satellite (HW8). Overall, the MMCR-derived CBHs are slightly higher (by 0.08 km) than those derived from the CL51. By contrast, the MMCR-derived CTHs are significantly higher (by 0.82 km) than those retrieved from the HW8 satellite. In the presence of precipitation, the MMCR-derived cloud boundaries are generally lower than those obtained by the CL51 due to the much larger rain-induced attenuation of MMCR signals. In particular, the discrepancy between MMCR- and CL51-derived CBHs decreases with rainfall intensity, as opposed to CTHs from the MMCR and the HW8 satellite that increase with rainfall intensity. CL51 and HW8 data can be used to complement MMCR data when there is rainfall or when MMCR data is missing. This enables the development of a seasonal cloud climatology for Beijing. CTHs reach a peak in summer, and CBHs are lowest in winter. The observed cloud properties reported here will not only facilitate future cloud forcing studies but also provide a validation data source for climate models. Highlights: The vertically-resolved cloud structures in Beijing are elucidated using MMCR, ceilometer and Himawari-8. MMCR-derived cloud base is slightly higher than that from CL51, as opposed to cloud top from MMCR and HW8. The rainfall impact has been analyzed on MMCR-derived cloud base height and top height.